Applications of Fern Dipteris Conjugate in Anti-bacterial and Anti-lipolytic Purpose - Jarial, Rini; Singh, Lakhveer; Thakur , Sevta; Zularisam, A. W.; Mimi Sakinah, A. M.; Kanwar, S. S. (Universiti Malaysia Pahang, 2016)
The aim of the present study was to assess the biological properties of Dipteris conjugate and to identify its functional compounds. The methanolic leaves-extract (MLE) of D. conjugate at different concentrations 5 to 30 µg/ml were assessed for anti-bacterial activities by measuring inhibition zones against a panel of pathogenic bacterial strains using agar diffusion method. MLE at a concentration of 25 µg/ml showed marked anti-bacterial activity against all bacterial strains (11-25 mm zone of inhibition) and was maximum against Staphylococcus aureus (25 mm). The MLE of had the best MIC values of 2.25 and 9.0 mg/ml against S.aureus and Enterobacter sp., respe D. conjugate actively. The MLE also possessed good antilipolytic activity (55%) against a porcine pancreatic lipase (PPL) and cholesterol oxidase inhibition (69%).The present study provided strong experimental evidences that the MLE of D.conjugate is not only a potent source of natural anti-oxidants and anti-bacterial activity but also possesses efficient cholesterol degradation and anti-lipolytic activities that might be beneficial in the body weight management. The results suggest that MLE of D. conjugate could potentially be employed in traditional medicine as they are rich in compounds with anti-oxidant, anti-microbial and anti-lipolytic properties.